innovation and cultural marginalization Their impact on Kurdish identity - Rashid, L.Dr. Shamal Latif (Sulaimani Journal for Humanities, 2025)
Innovation and cultural marginalization are complex phenomena that are evident in the present era. When a society moves towards modernity, some traditional cultures are threatened with neglect, marginalization and even extinction. This process occurs naturally, but there are a number of motives that accelerate this process and negatively affect cultural identity. When this natural phenomenon is transformed into cultural occupation and marginalization through domination and monopoly, the negative impact on national and social identity increases. When a dominant and powerful culture tries to marginalize another culture with a colonial, ideological, racial or religious agenda, it deactivates the marginalized culture and leads to its dissolution. Also, many times the values and traditions that have developed over hundreds of years have been beneficial to society. The dominance of global culture as a result of the development of modern material processes is a fundamental factor in the marginalization and occupation of local culture at the level of language, art, daily life, traditional and social values. This paper attempts to illustrate the factors and motivations that make this process possible, presenting some examples and illustrations in terms of theory and practice. The idea behind this research is to show the conditions of opening the door of global and regional cultural domination on Kurdish cultural identity and the desire of Kurdish people to separate from their own culture and receive the cultural identity of the dominant nation. The act of preserving Kurdish identity is explained and presented through the theory of cultural resistance, the post-colonial paradigm and the method of cultural criticism.
Keywords: Cultural hegemony; cultural marginalization; cultural resistance; identity maintenance